Uji Coba Pembuatan Genoise Cake dengan Menggunakan Kelapa Sebagai Subtitusi Tepung - Salim, Chairul; Vienna Artina Sembiring; Bianca Natasha (Pusat Penelitian & Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2024)
Genoise cake is a sponge cake that originates from Italy. Making Genoise Cake uses the Au Bain Marie method, where the egg beater container is immersed in another container filled with warm water while the eggs are beaten until the eggs feel warm. The result of a genoise cake is a light and fluffy cake. So far, the raw material for making genoise cake is wheat flour, we can reduce the use of wheat flour and provide variations to genoise cake by using coconut flour as the raw material for making genoise cake. This research was conducted to find out whether coconut flour can be used as a substitute in making genoise cake, and this research was also to find out whether there were differences in terms of taste and texture. This research used an experimental method of one control product and three treatments. Data was obtained by distributing questionnaires to two groups, namely untrained panelists and expert panelists. The results obtained from panelists were not surveyed to find out whether this product was acceptable to the public and the results from expert panelists were to find out whether there were differences in terms of taste and texture. The research results showed that in terms of taste, panelists were not trained to prefer the 90% coconut flour substitution and for texture, panelists were not trained to prefer the 100% wheat flour control. Expert panelists prefer 100% control in terms of both taste and texture.